Soft tissue cephalometric analysis applied to Himachali ethnic population - Isha Aggarwal; Anil Singla (Wolters Kluwer Medknow Publications, 2016)
Introduction: The modern society considers facial attractiveness as an important physical attribute. The great variance in soft tissue drape of the human face complicates accurate assessment of the soft tissue profile, and it is a known fact that facial features of different ethnic groups differ significantly. This study was undertaken to establish norms for Himachali ethnic population. Materials and Methods: The sample comprised lateral cephalograms taken in natural head position of 100 normal individuals (50 males, 50 females). The cephalograms were analyzed by Arnett soft tissue cephalometric analysis for orthodontic diagnosis and treatment planning. Student's t-test was used to compare the means of the two groups. Results: Statistically significant differences were found between Himachali males and females in certain key parameters. Males have thicker soft tissue structures and a more acute nasolabial angle than females. Males have longer faces and females have greater interlabial gap and maxillary incisor exposure. Males have more deep-set facial structures than females. Conclusions: Statistically significant differences were found between Himachali males and females in certain key parameters. Differences were also noted between other ethnic groups and Himachali faces.